Koreo-Japonica : a re-evaluation of a common genetic origin - Vovin, Alexander (Hawaiʻi studies on Korea., 2010)
The Japonic (Japanese and Ryukyuan) portmanteau language family and the Korean language have long been considered isolates on the fringe of northeast Asia. This text challenges a view widely held by Japonic and Korean historical linguistics on the relationship between the two language families.